Colon perforation caused by transanal decompression tube after laparoscopic low anterior resection: A case report. (March 2021) - Hiraki, Masatsugu; Tanaka, Toshiya; Okuyama, Keiichiro; Kubo, Hiroshi; Ikeda, Osamu; Kitahara, Kenji
Highlights: The effectiveness of a transanal decompression tube to prevent anastomotic leakage after rectal surgery is widely accepted. A rare complication of colonic perforation due to a transanal decompression tube may occurred. The relationship between the tip of the transanal decompression tube, the intestine and the sacrum might be important. Abstract: Introduction: The effectiveness of transanal decompression tube (TDT) to prevent anastomotic leakage after rectal surgery has been widely accepted in recent years. However, a rare complication of intestinal perforation due to TDT has been also reported. Presentation of case: A 88-year-old woman underwent laparoscopic low anterior resection for rectal cancer. An abdominal drainage tube adjacent to the colorectal anastomosis and a TDT were placed. The patient experienced abdominal pain, nausea and elevated inflammatory markers on postoperative day 6. Enema and computed tomography demonstrated colonic perforation due to the TDT, and emergency laparotomy was performed. Perforation of the anterior sigmoid colon located at the proximal side of the colorectal anastomosis was seen, and the TDT was exposed to the abdominal cavity. Therefore, primary closure of the perforation site, peritoneal lavage, drainage tube placement and transverse colostomy was performed. Discussion: In our case, TDT seemed to compress the anterior wall of the colon and lead to perforation. The looseness of the remaining oral intestinal tract depressed in the pelvis was compressed by the TDT. Conclusion: TDTs should be very carefully placed to avoid complication. The length and looseness of the oral intestine and the relationship between the TDT to be inserted might be important.